Effects of Danshensu and Salvianolic Acid B from Salvia miltiorrhiza Bunge (Lamiaceae) on Cell Proliferation and Collagen and Melanin Production - Yi-Shyan Chen; Shu-Mei Lee; Ying-Ju Lin; Shu-Hua Chiang; Chih-Chien Lin (Molecules, 2014)
Danshensu (DSU) and salvianolic acid B (SAB) are the primary water-soluble compounds of Salvia miltiorrhiza Bunge (Lamiaceae). In this study, we analyzed the effects of DSU, SAB and a S. miltiorrhiza extract (SME) on cell proliferation. Additionally, the effects of DSU and SAB on collagen synthesis in Detroit 551 human normal fibroblast cells and on melanin production in B16 melanoma cells were verified. The results demonstrated that SME can enhance the proliferation of Detroit 551 cells and that this boost may be caused by DSU and SAB. This research showed that SME, DSU and SAB all have the ability to increase the production of collagen in Detroit 551 cells. The results also confirmed that DSU and SAB can attenuate the α-MSH-stimulated melanin production of B16 cells by inhibiting tyrosinase activity. Therefore, SME, DSU and SAB each have the potential to be utilized as active ingredients in wound healing or cosmetic treatments. In the future, DSU and SAB could also be used as functional components for treating hyperpigmentation.